1905 N.J. Laws 324-25 - (:unkn) unknown (My University, 1905)
Ch. 172, 1: Prohibited the carrying of a concealed revolver, pistol or other deadly, offensive or dangerous weapon or firearm or any stiletto, dagger or razor. Punishable by fine up to $200 and/or imprisonment with hard labor up to 2 years.
Keywords: CARRY - CONCEALED